Advanced deposition of hard a-C:Me coatings by HPPMS using Ne as process gas - Bobzin, K.; Brögelmann, T.; Kruppe, N.C.; Engels, M. (Surface & coatings technology, 2017)
Diamond-like carbon (DLC) coatings are used in numerous tribological applications, for example on highly-loaded components of the automotive powertrain. The high hardness and low roughness of these coatings contribute to the reduction of the component wear in tribological contact. It has been shown that hard a-C coatings with a low roughness can be deposited by means of high power pulsed magnetron sputtering (HPPMS) using Ne as process gas. Furthermore, the doping of a-C coatings with metals is the subject of current research. These a-C:Me coatings exhibit significant changes of the coating properties, which might contribute to a performance increase in tribological applications. Hence, in the present work a-C:Me coatings were successfully deposited in a high-volume semi-industrial coating unit by means of a hybrid process using one direct current magnetron sputtering cathode with a Zr target and one HPPMS cathode with a graphite target, using Ne as process gas. Furthermore, coatings were deposited using two HPPMS cathodes. The deposition of coatings using both types of processes was conducted in order to evaluate the influence of dcMS and HPPMS on the coating properties and the economic efficiency of both processes, respectively. The average power of the cathode with the Zr target was varied in the dcMS mode and in the HPPMS mode, whereas the cathode with the C target was powered constantly in HPPMS mode. A densification of the microstructure was observed for the HPPMS processes. Furthermore, different ratios of C and Zr in the coating were obtained, which resulted in a varying phase composition. Coatings with a maximum universal hardness HU=25GPa and arithmetic mean roughness Ra=0.03μm could be deposited. •Deposition of a-C:Zr coatings by dcMS/HPPMS hybrid HPPMS processes is possible.•Nanocomposite structure of ZrC grains in a-C matrix can be assumed.•A maximum universal hardness HU=25GPa was achieved for HPPMS processes.•Coating properties were correlated with results by means of plasma diagnostics.•HPPMS does not improve a-C:Zr coating properties, compared to PCAE and PLD.